Using cloud technology in a virtual learning environment (Journal of Educational Sciences, 2023)
The article presents an experience of teaching using a private cloud platform for blended learning. The learning platform is implemented using cloud computing technologies. The research topic is relevant for educational institutions that utilize cloud computing technologies. The aim of this work is to demonstrate the changes in the mechanisms of functioning and implementation of the education system in the context of virtual learning. The platform provides resources for the development of blended learning, such as video conferencing, chat, webinars, online tests, and surveys. The functionality of the private cloud platform is ensured by client-server technology. The authors believe that the use of private cloud platforms is justified as it enables the activation of students' activities, improves the quality of education, enhances the professional level of teachers, and diversifies the learning format.In the empirical study, 41 students of al-Farabi Kazakh National University participated. The students were offered training on the developed platform using a blended learning approach for several disciplines. To assess the significance of the research results, the two-sample t-test was used.The hypothesis of statistically significant differences between the average academic performance in the experimental and control groups before and after the implementation of the online platform was confirmed. After the implementation of the online platform, the students' results improved.Keywords: cloud computing, teaching platform, virtual environment, mixed learning method.